ТАРИХИЙ ШАХСЛАР ОБРАЗИ ВА БАДИИЙ ТАЛҚИН (Гулистон Матёқубова ижоди мисолида) - Қурамбаева, Г. (SCIENCE and SOCIETY, 2018)
The article deals with the analysis of the skill of People's poetess of Karakalpakstan G. Matyakubova in creating the images of historical figures.
Keywords: historical drama; poem; image; theme; prototype; lyric depicting; epic direction; conflict; true life; literary genre; literary artistic interpretation